Tre slags panenteisme: et forsøg på en begrebsafklaring - Gregersen, Niels Henrik (Dansk Teologisk Tidsskrift, 2009)
It is argued that panentheism, attractive as it is, is far from stable. Also Aquinas and Spinoza occasionally used the expression that “all things exist in God”. Moreover, the world’s presence in God can be construed in different ways, as a locative presence (the container model), as a realization of a wider set of divine possibilities (the quasi-mathematical model), or as a mental presence (the consciousness model). I nonetheless propose a generic concept of panentheism, defined by the features that the world is somehow contained in God, and that there is a two-way relation between God and world. On this basis, the article offers a typology of (1) a soteriological panentheism reconstructed on the basis of classic Trinitarian thought, (2) an expressivist panentheism developed in post-Kantian philosophical theology, and (3) a dipolar panentheism in continuation of Whitehead. My conclusion is that dipolar panentheism is not compatible with the two other forms of panentheism, and that a metaphysical choice has to be made between them.